Redox-Active Metabolites as Clinical Biomarkers: A Comprehensive Review of Mechanisms and Diagnostic Applications - Raffik, Daroon Essam; Mohammed, Batool Khalil; Shawkat, Zainab Adnan (American Journal of Biomedicine and Pharmacy, 2025)
Key modulators of cellular metabolism and oxidative stress are redox-active metabolites, such as glutathione (GSH/GSSG), flavin adenine dinuucleotide (FAD/FADH₂), thioredoxin, nicotinamide adenine dinucleotide (NAD + / NADH), and nicotinamide adenine dinuucleotide phosphate (NADP+/ NADPH). Recent developments in precision medicine and metabolomics have demonstrated their vital functions as dynamic biomarkers for metabolic diseases, cancer, neurodegeneration, and cardiovascular disease. This thorough assessment synthesizes current information by methodically analyzing 155 peer-reviewed publications from the pubMed, Scopus, and Web of Science databases (2020-2025). Nuclear magnetic resonance spectroscopy, electrochemical biosensors, and ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) are among the analytical advances we assess. Diagnostic performance across major illness categories is demonstrated by a meta-analysis of 87 clinical studies (n=28, 447 patients), with area under the curve values ranging from 0.78 to 0.94. Standardization gaps, inter-laboratory variability (CV 15-35%), and cost issues ($50-200 each test) are major obstacles. On the other hand, Al-driven interpretation and new point-of-care technologies hold potential for clinical use. Standardization will be addressed by global initiatives and extensive validation studies, establishing redox metabolites as trustworthy indicators for precision medicine.